Naphthoquinone glycosides for bioelectroanalytical enumeration of the faecal indicator Escherichia coli - Hinks, Jamie (John Wiley and Sons Inc., 2016)

(untitled) (Microb Biotechnol)
Microbial water quality monitoring for the presence of faecal indicator bacteria (FIB) is a mandatory activity in many countries and is key in public health protection. Despite technological advances and a need for methodological improvements, chromogenic and fluorogenic enzymatic techniques remain the mainstays of water quality monitoring for both public health agencies and regulated utilities. We demonstrated that bioelectroanalytical approaches to FIB enumeration are possible and can be achieved using commercially available enzyme‐specific resorufin glycosides, although these are expensive, not widely available or designed for purpose. Following this, we designed two naphthoquinone glycosides which performed better, achieving Escherichia coli detection in the range 5.0 × 10(2) to 5.0 × 10(5) CFU ml(−1) 22–54% quicker than commercially available resorufin glycosides. The molecular design of the naphthoquinone glycosides requires fewer synthetic steps allowing them to be produced for as little as US$50 per kg. Tests with environmental samples demonstrated the low tendency for abiotic interference and that, despite specificity being maintained between β‐glucuronidase and β‐galactosidase, accurate enumeration of E. coli in environmental samples necessitates development of a selective medium. In comparison to a commercially available detection method, which has U.S. Environmental Protection Agency (EPA) approval, our approach performed better at high organism concentrations, detecting 500 organisms in 9 h compared with 13.5 h for the commercial method. Bioelectroanalytical detection is comparable to current approved methods and with further development could result in improved detection times. A recent trend for low‐cost open‐source hardware means that automated, potentiostatically controlled E. coli detection systems could be constructed for less than US$100 per channel.